Analysis of sudan I, sudan II, sudan III, and sudan IV in food by HPLC with electrochemical detection: Comparison of glassy carbon electrode with carbon nanotube-ionic liquid gel modified electrode - Orawon Chailapakul (2018)
A method was developed for analyzing of sudan I, sudan II, sudan III, and sudan IV by high performance liquid chromatography coupled with an electrochemical detector. The electrochemical oxidation of each compound was investigated with a carbon nanotube-ionic liquid gel modified glassy carbon (MWNTs-IL-Gel/GC) electrode using cyclic voltammetry. The results were compared with those of glassy carbon electrodes. At the MWNTs-IL-Gel/GC electrode, highly reproducible, well-defined cyclic voltammograms for sudan oxidation were obtained. In the flow system, MWNTs-IL-Gel/GC exhibited highly reproducible and well-defined amperometric signals without peak tailing. In addition, the determination of sudan dyes by mean of isocratic reverse-phase HPLC, with amperometric detection at MWNTs-IL-Gel/GC and GC electrode, have been investigated. The chromatograms showed excellent separation. The detection limits ranged from 0.001 to 0.005 ppm. The method was sensitive, selective and could be applicable for the assay of sudan dyes in soft drink samples. © 2008 Elsevier Ltd. All rights reserved.